Nhận thức của sinh viên sư phạm Toán về đánh giá quá trình: Một nghiên cứu trường hợp tại Trường Đại học Giáo dục - Đại học Quốc gia Hà Nội - Đào, Thị Hoa Mai (Tạp chí Giáo dục, 2024)
The research was conducted to survey the awareness of mathematics education students about formative assessment, particularly in the context of reforming the general education program with an orientation towards increasing diverse forms of assessment, focusing on formative assessment. A case study was conducted with students majoring in Mathematics Education who are in their third and fourth years at the VNU University of Education. A survey tool was designed, including 30 observed variables for 6 survey aspects concerning students’ perceptions of formative assessment. Data were processed from 228 responses, with the Cronbach’s alpha coefficient measuring the reliability of the survey tool being 0.867. Analysis of the survey data shows that mathematics education students’ understanding of formative assessment, although quite good, is not comprehensive. Students’ awareness of some aspects related to formative assessment differs between those who have not yet studied and those who have or are currently studying some modules with content related to formative assessment, as well as between third-year and fourth-year students. These result predict students’ understanding of formative assessment and their ability to implement it in teaching practice after graduation.